Preference-Choice Mismatch and University Dropout - Didier Fouarge; Pascal Heß (Institute of Labor Economics (IZA), 2023)
Drawing on data from the German National Educational Panel Study (NEPS), we show that students who select majors that do not match their occupational preferences prior to enrolling in university are more likely to drop out than those who do choose majors that match their occupational preferences. Our findings suggest that this gap cannot be explained by institutional obstacles to entering a major. Instead, the primary mechanisms behind this phenomenon are indecisiveness and preference changes.
Keywords: J24; D83; 330; dropout; preferences; mismatch; tertiary education